Varying Youth Cohort Effects on Regional Labour Market Outcomes in Germany - Thomas de Graaff; Ceren Ozgen; Duncan Roth (Institute of Labor Economics (IZA), 2018)
We assess how changes in youth cohort sizes effect employment rates in German labour market regions. Replicating the conventional approach, we estimate that a percentage increase in the youth share reduces regional employment rates by -0.2%. We challenge the assumption that cohort size effects are homogenous across space and find robust evidence that the negative effect of youth cohort size is more pronounced in the labour markets of metropolitan regions. These results suggest an upward pressure on urban regional employment rates as a result of the projected decrease in the size of the German youth share.
Keywords: J1; J2; R1; R2; 330; employment rate; youth share; Germany; regional heterogeneity